2020
DOI: 10.47405/mjssh.v5i5.403
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Behaviour in Green Purchasing: A Case Study in Petaling Jaya, Malaysia

Abstract: Malaysia faces several environmental issues, such as rising sea levels, water pollution, air pollution, climate changes, acid rain and soil erosion for the past few years. It is important to save the environment because by doing so, it will not only attract more tourists from foreign countries to come for vacation in Malaysia, but it also encourages manufacturers and consumers to support green product. Therefore, Malaysia should allocate the use of green products in daily life. Still, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
1
3
1
Order By: Relevance
“…Affordability has a positive but insignificant influence on purchase intention (H3), thus not supporting the H3. These findings contradict the previous study that Khuzaimah et al (2020) conducted, where affordability is the most significant factor influencing purchase intention. Environmental awareness also positively affects but is insignificant towards purchase intention (H1), which means the H1 is rejected.…”
Section: Resultscontrasting
confidence: 99%
“…Affordability has a positive but insignificant influence on purchase intention (H3), thus not supporting the H3. These findings contradict the previous study that Khuzaimah et al (2020) conducted, where affordability is the most significant factor influencing purchase intention. Environmental awareness also positively affects but is insignificant towards purchase intention (H1), which means the H1 is rejected.…”
Section: Resultscontrasting
confidence: 99%
“…Specifically, both price and environmental concern were able to predict intention with variance increased to 93 percent, which indicated the importance of environmental concern after perceived behavioral control. The significant effect of environmental concerns on behavioral intentions is also supported by previous studies (Khuzaimah et al, 2020;Aman et al, 2012;Albayrak et al, 2013;Maichum et al, 2016;Han et al, 2010). These findings reinforce the important contribution of environmental concerns to green purchasing behavior.…”
Section: Discussionsupporting
confidence: 83%
“…As investigation costs escalate, the manufacturer's decision nudges consumers away from investigating, leading to direct purchases. Khuzaimah et al 60 , through empirical research on the Malaysian consumer market, confirmed the viewpoint that consumers might choose to purchase green products without fully understanding the environmental benefits of such products. In some specific valuation intervals, higher investigation costs may enhance consumer utility via increased product greenness and bolster manufacturers' profits through increased pricing.…”
Section: Discussionmentioning
confidence: 91%